Covid Pandemic in an Unequal world - Campani, Giovanna; Di Grigoli, Antonio Raimondo (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
This video reports the recording of the webinar that took place last December 14, 2020 for the presentation of number 10 of the magazine entitled "An Eniqual word facing the Covid-19 Pandemic". The event was organized by the director of the magazine Giovanna Campani and the managing editor, Antonio Raimondo Di Grigoli and moderated by the scholar Francesco Gervasi (Universidad Autónoma de Coahuila, Messico). The webinar addressed the issue of the causes and consequences generated by the new Covid-19 virus, from an international and interdisciplinary perspective given the varied geographical and disciplinary origin of the scholars who took part in the webinar. Starting from the speakers' exposition of their research on the delicate problems caused by the pandemic and, in particular, on gender inequalities in a global perspective, it was possible to open a fruitful debate on the different perspectives on political and social decisions in particular in Latin America and in Italy, but not only and of the possible solutions.